Особливості обстановки шахрайства, вчиненого організованою злочинною групою у сфері житлового будівництва - Опанасенко, Н. О.; Opanasenko, N. O. (Вісник Харківського національного університету внутрішніх справ. - 2016. - № 2 (73). - С. 69-75., 2016)
Проаналізовано обстановку вчинення злочину як важливий елемент криміналістичної характеристики. Розкрито практичне значення дослідження обстановки шахрайства. Виявлено та охарактеризовано особливості обстановки шахрайства, вчиненого організованою злочинною групою у сфері житлового будівництва.

Circumstances of fraud committed by an organized criminal group in the sphere of housing construction have been researched. It is emphasized that circumstances of committing a crime is one of the important and obligatory elements of forensic characteristics of crimes of the specified type. The article’s objective is to analyze the circumstances of committing a crime as an important element of forensic characteristics, as well as identification and characteristics of the features of circumstances of fraud committed by organized criminal groups in the sphere of housing construction. The author has emphasized that circumstances of fraud committed by an organized criminal group in the sphere of housing construction are characterized both by a set of socio-economic conditions in a certain period of time, and a set of phenomena and processes that directly surrounded swindlers at the moment of crime commission in certain conditions of a place and time. In some cases, swindlers use circumstances that exist in the housing construction sphere, in others – they change the existing circumstances of committing the offense or they create favorable circumstances themselves. It is indicated that circumstances of committing a crime are in constant relationship with other elements of forensic characteristics. It has been concluded that the data about circumstances of committing a crime assists to determine the modus operandi, to identify the personal traits of criminals and to obtain information about the mechanism of a crime in general.

Проанализирована обстановка совершения преступления как важный элемент криминалистической характеристики, раскрыто практическое значение исследования обстановки мошенничества. Выявлены и охарактеризованы особенности обстановки мошенничества, совершённого организованной преступной группой в сфере жилищного строительства.
Features of the circumstances of fraud committed by an organized criminal group in the housing construction sphere
Особенности обстановки мошенничества, совершённого организованной преступной группой в сфере жилищного строительства
Опанасенко, Н. О. Особливості обстановки шахрайства, вчиненого організованою злочинною групою у сфері житлового будівництва / Н. О. Опанасенко // Вісник Харківського національного університету внутрішніх справ. - 2016. - № 2. - С. 69-75.
Опанасенко Н. О. "Особливості обстановки шахрайства, вчиненого організованою злочинною групою у сфері житлового будівництва." Вісник Харківського національного університету внутрішніх справ 2 (2016): 69-75.
Opanasenko, N.O. (2016), “Features of the circumstances of fraud committed by an organized criminal group in the housing construction sphere” [Osoblyvosti obstanovky shakhraistva, vchynenoho orhanizovanoiu zlochynnoiu hrupoiu u sferi zhytlovoho budivnytstva], Visnyk Kharkivskoho Natsionalnoho Universytetu Vnutrishnikh Sprav, No. 2, pp. 69-75.
Keywords: Криміналістика. Criminalistics. Криминалистика; Наукові публікації. Scientific publications. Научные публикации; Україна. Ukraine. Украина; шахрайство; житлове будівництво; обстановка вчинення шахрайства; організована злочинна група; криміналістична характеристика злочинів; fraud; housing construction; circumstances of committing fraud; organized criminal group; forensic characteristics of crimes; criminal law characteristics; мошенничество; жилищное строительство; обстановка совершения мошенничества; организованная преступная группа; криминалистическая характеристика преступлений